CRRT: trattamento della crisi metabolica grave nella maple syrup urine disease. Issue 1 (March 2018) - Fatuzzo, Pasquale; Marchese, Rossella R; Aliotta, Roberta; Pani, Alessandra; Zanoli, Luca
Maple syrup urine disease (MSUD) is a rare disorder of the amino acid metabolism that is transmitted as an autosomal recessive trait and is characterized by deficiency of the branched-chain α-keto acid dehydrogenase enzyme complex (BCKDC). Reduced BCKDC activity results in increased plasma concentrations of leucine, isoleucine and valine. Leucine storage is mainly accountable for clinical symptoms within 48 hours of birth, more infrequently later in life. In subsequent years, patients with MSUD can develop acute metabolic decompensation, which may manifest as lethargy and/or coma, along with a high risk of cerebral edema and exitus. Sudden treatment of acute metabolic disorders is required: suppression of catabolism and utilization of amino acids in excess for protein synthesis and prompt removal of accumulated toxic metabolites by extracorporeal techniques (intermittent hemodialysis, continuous renal replacement therapies, peritoneal dialysis) or exchange transfusion. We discuss the case of a 14-year-old patient suffering from MSUD who was hospitalized for acute metabolic failure. The patient was at first treated only with nutritional support, and then with continuous veno-venous hemofiltration (CVVH) for severe neurological involvement.